The Development Ethnic Value of Mandar in Syair Passayang-Sayang - Jafar, Jafar; Supratno, Haris; Sudikan, Setya Yuwana (Budapest International Research and Critics University, 2020)
The purpose of this study is to find and describe (1) the use of Mandar ethnic values in the Passayang-Sayang songs of the 1960-1970 period, (2) the use of the Mandar ethnic values in the Passayang-Sayang songs period of 1970-1980, (3) the use of the Mandar ethnic values in the Passayang-Sayang song period of 1980-1990, (4) the use of Mandar ethnic values in the Passayang-Sayang song period of 1990-2000, (5) the use of the Mandar ethnic value in the Passayang-Sayang song period of 2000-2010, and (6 ) the use of the Mandar ethnic value in the song of the Passayang-Sayang period 2010-Present. The theory used in this research is the theory of literary geography put forward by Herder, Stael, and Ricardson. This research is a qualitative descriptive study. The research data are in the form of Passayang-Sayang Mandar poetry texts, informant statements, and facts in the field. Data collection activities carried out by observation and observation techniques, interviews, recording, recording, and documentation. In this study the researcher acted as a key instrument guided by data collection guidelines. Data analysis procedures use the spiral model, while data analysis uses objective hermeneutics. To avoid research bias, triangulation was carried out for each stage of the study, research tools, and clarification of research findings to the informants as poet owners, Focus Group Discussions, and external audits. The findings of this study are the development of ethnic values in the Passayang-Sayang Mandar poem in the form of (16) ethnic values found in the period 1960-1970, (5) ethnic values found in the period 1970-1980, (7) ethnic values found in the 1980 period -1990, (6) ethnic values were found in the period 1990-2000, (7) ethnic values were found in the period 2000-2010, (8) ethnic values were found in the period 2010-Now.